Gear Surface Design and Contact Analysis of Cycloid Bevel Gear based on Deviation Tooth Surface - Yang Jianjun; Chen Penghui; Nie Shaowu; Zhang Hua; Xu Kai (Jixie chuandong, 2018)
In order to improve the meshing performance of cycloid bevel gear made by precision forging,the modification method of gear based on the deviation surface is proposed. Taking the pinion tooth surface of the cycloid bevel gear as the generating surface,the conjugating gear tooth surface equation satisfied the pre-determined transmission relationship is obtained according to the meshing principle. Based on the predesigned deviation surface with certain contact characteristics,the target tooth surfaces of gear can be obtained by superposing the deviation surfaces over the conjugate gear tooth ones. The finite element contact analysis is applied to the modification design for contact path in different directions. The simulation results show that bias correction is better than the others considering the flank contact stress,root tensile stress and contact pattern. The proposed modification method provides design reference for precision forging of the cycloid bevel gear.